Models of Dementia: an introductory overview. (20th July 2011) - Graham, Lindsay; Sutherland, Calum
Abstract : The analysis of the molecular development of AD (Alzheimer's disease) is technically challenging, due to the chronic nature of the disease, the lack of early and definitive clinical diagnosis, and the fact that the abnormal molecular pathology occurs in the brain. Therefore appropriate animal models of AD are essential if we are to dissect the processes leading to molecular pathology, and ultimately to test the efficacy of potential therapies before clinical studies. Unfortunately, there is controversy over the benefits of the available models, the only consensus of opinion being that no perfect model currently exists. The investigation of animal models is extremely costly and time-consuming, therefore researchers tend to focus on one or two models. For scientists entering the AD research field, it can be difficult to identify the most appropriate model for their needs. Therefore the Models of Dementia: the Good, the Bad and the Future Biochemical Society Focused Meeting provided a platform for discussion and debate on the use and limitations of current models, the most appropriate methods for their characterization and identification of the most pressing needs of the field in general.